Intersections of Inequality, Migration and Diversification
XVII, 164 p. 18 illus. in color.
Keywords: “This collection provides critical new qualitative and quantitative analyses of migration and inequality that take intersectionality seriously. Essential reading for migration studies students and scholars.” —Shanthi Robertson, Institute of Culture and Society, Western Sydney University, Australia “This edited volume is a ground-breaking contribution, demonstrating that migration shapes, and is shaped, by dimensions of inequality at various scales and in intergenerational perspective.” —Adele Garnier, Department of Modern History, Politics and International Relations, Macquarie University, Australia “This book is a high quality original contribution to an understanding of migration, diversity and inequality in New Zealand. It brings together some of the latest thinking on MDI and contextualizes it for New Zealand.” —John Connell, School of Geosciences, University of Sydney, Australia This book examines the relationship between migration, diversification and inequality in Aotearoa/New Zealand. The authors advance a view of migration as a diversifying force, arguing that it is necessary to grapple with the intersection of group identities, state policy and economic opportunities as part of the formation of inequalities that have deep historical legacies and substantial future implications. Exploring evidence for inequality amongst migrant populations, the book also addresses the role of multicultural politics and migration policy in entrenching inequalities, and the consequences of migrant inequalities for political participation, youth development and urban life. Rachel Simon-Kumar is Associate Professor in the School of Population Health at the University of Auckland, New Zealand. Francis L. Collins is Professor of Geography at the University of Waikato, New Zealand. Wardlow Friesen is Associate Professor of Geography at the University of Auckland, New Zealand.